Assessment of Different Methodologies for Mapping Urban Heat Vulnerability for Milan, Italy. (June 2019) - Bhattacharjee, S; Gerasimova, E; Imbert, C; Tencar, J; Rotondo, F
Abstract: Aims: To compare methodologies for calculating vulnerability index of Milan city and find correlation between the main components influencing vulnerability. Methodology: At-satellite brightness temperatures were used to study exposure of city districts to Urban Heat Island. The distribution of vulnerable population (people younger than 14 and older than 65) was also taken into account by producing a map, which showed sensitivity indices for each city district. Adaptive capacity was represented as a complex set of subindicators such as health care accessibility, level of living conditions and vegetation cover. Exposure, sensitivity and adaptive capacity – main indicators of vulnerability – were used to obtain five different maps, which could identify districts more vulnerable to the Urban Heat Island. Collected data showed correlations between factors influencing vulnerability. Results: All formulas except one show similar vulnerability index distributions. Correlation graphs showed direct proportionality with exposure, very low correlation with sensitivity and indirect proportionality with adaptive capacity (except one formula which is discussed in paper).